An Analysis of Syntax and Academic Word Choice in Political News - Theangpitak, Wannarak (IJRDO- Journal of Educational Research, 2017)
English newspapers contain discourses with a variety of language usage from the real world. Therefore, English newspapers could be utilized as authentic materials in an English study program or course to support English learning and teaching. This study aimed to explore a deeper insight how English grammatical structures and academic word choices used in an English newspaper, based on Systemic Functional Grammar (SFG) by Michael Halliday and Academic Word List (AWL) by Averil Coxhead. The research results showed that the newspaper presented a variety of English sentences used in spoken and written discourses in the context of articles. Complex sentences were mostly utilized as a versatile writing technique. The academic words were accounted for 7.69% of the total words in the 250 news articles, and the most frequently presented words were “constitute” and “draft”. Some word families were not found from the news articles; this might be due to some reasons that those words were likely irrelevant to political affairs or situations in the period of study such as “nuclear,” “medium,” or “series.”